Les inondations à Nancy – Anciennes et nouvelles problématiques - Emmanuel Chiffre; Denis Mathis; Anne Mathis (Développement Durable et Territoires)
May 21, 2012, the greater metropolitan area of Nancy knew an exceptional wet episode with consequent flooding by runoff. Yet the city had big work getting out of water in the area between Meurthe and Canal. Built in the floodplain of the river, this industrial and working-class district was the most vulnerable. Floods regularly affected this space and leading to its decline. The proximity of the river, the memory as much as vulnerability to the risk of flooding have weighed on the future of the district. Since 1986, protection work helped to renovate this space and to reconcile Nancy with their river. Now, this district forms a revitalized waterfront and a model for the whole of the urban area.